Volume Equations for Abies borisii-regis Mattf. and Fagus sylvatica L. in central Greece - Georgios Dais; Kyriaki Kitikidou; Elias Milios (Annals of Silvicultural Research, 2022)
In the mixed stands of Fagus sylvatica - Abies borisii-regis in Aspropotamos (central Greece), 90 fir trees and 87 beech trees were randomly selected. Breast height diameter, total tree height and form factor were measured to the sampled trees, while 14 single-entry and 18 double-entry volume models were fitted to data. No double-entry model is selected for either species. The selected singleentry models for the estimation of the A. borisii-regis and F. sylvatica volume fit very well (R2>0.8), while the comparison of the two volume estimation curves reveals that fir has a larger volume than beech, when their diameter is the same. Fir has a mean form factor of 0.331, while beech has a mean form factor of 0.315. The observed form factor differences and different patterns in form factors between the two species can be the result of the differences in their growth (form and ecology).